2022
DOI: 10.3390/ijms23126738
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Approach to Elucidate the Changes in Saliva and Serum Proteins of Pigs with Septic and Non-Septic Inflammation

Abstract: Sepsis is a systemic inflammatory response triggered by an infectious agent and is recognized by the World Health Organization as a global concern, since it is one of the major causes of severe illness in humans and animals. The study of the changes that can occur in saliva and serum in sepsis can contribute to a better understanding of the pathophysiological mechanisms involved in the process and also to discover potential biomarkers that can help in its diagnosis and monitoring. The objective of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 49 publications
(50 reference statements)
6
21
0
Order By: Relevance
“…Overall, in our report, we found changes in proteins in saliva related to inflammation and the immune system, as have been described in saliva in pigs with sepsis experimentally induced by LPS administration and other infectious diseases such as S. suis infection [ 3 , 4 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Overall, in our report, we found changes in proteins in saliva related to inflammation and the immune system, as have been described in saliva in pigs with sepsis experimentally induced by LPS administration and other infectious diseases such as S. suis infection [ 3 , 4 ].…”
Section: Discussionsupporting
confidence: 77%
“…It has been observed that saliva can show proteomic changes in sepsis experimentally induced by lipopolysaccharide (LPS) administration in pigs [ 3 ]. Aldolase A and serpin 12 were proteins in saliva that were significantly upregulated in sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study that describes changes in biomarkers of redox status in pigs with sepsis. The pigs in our study showed, after LPS administration, increased body temperature as well as increased white blood cell count and C-reactive protein ( Table S2 ), and the presence of symptoms, such as depression, lethargy, and increased respiratory rate; which proved the validity of LPS administration as a model for sepsis in pigs, as has been previously described [ 21 , 25 ].…”
Section: Discussionsupporting
confidence: 86%
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/antiox11071380/s1, Table S1: Description of the basis and reagents of each assay performed in the study; Table S2: Rectal temperature, white blood cell count (WBC), and C-reactive protein (CRP) of each animal included in the study before and 3 and 24 h after injection of lipopolysaccharide (LPS), turpentine (TURP), and saline (control group). Data of LPS and TURP groups were previously described [25]; Spreadsheet S1: Raw data.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Currently, there are commercially available assays that allow the measurement of CALP [ 17 ] and aldolase [ 18 ], having the advantages associated with automation, such as higher precision and faster sample processing. The hypotheses of this work are that CALP and aldolase can be measured in the saliva of horses with commercially available assays and, furthermore, that these assays can detect the changes in these analytes that occur in horses with EGUS.…”
Section: Introductionmentioning
confidence: 99%